History and Language in Tennyson’s Tragedy Harold (1876) - M. Fahmi Saeed , Ismael; A. Dabbagh, Lanja (Al-Adab Journal, 2019)
Alfred Tennyson (1809- 1892) wrote a compact, action- packed, historical, patriotic, and a pioneering tragedy inspired by the Norman Conquest of England entitled Harold in 1876. It is based on the facts regarding the events leading to the Battle of Hastings in 1066. Tennyson has been, so far, the only man- of- letters to have dramatized this chapter of British history in a tragedy, even though he has never been the only writer to have paid attention to this turning- point in the destiny of his homeland. This tragedy focuses on the personal conflict between Harold Godwinson (1022- 1066) and William Duke of Normandy (1028- 1087), also known as William the Conqueror, or King William I. This drama, thus, is a journey to the past to explore the forces at work, and the men who made history, the struggle to achieve an improvement after the long- lasting social and cultural stagnation of England in Anglo- Saxon days which had lasted from 449- 1066. Tennyson chose the historical moment which all the earlier playwrights had avoided. Alongside this, he chose the accurate kind of discourse that would be more suitable for both the historical theme and the historical period.The paper considers and clarifies the notable presence of language and its use as an indication of the historical course of the work. This is carried out through the analysis of a number of selections from the text. The focus will be on the historical style of the dramatic discourse. Tennyson is faithful as much as possible not only to the events but to the historical kind of speech used by characters to make a convincing and trustworthy play linguistically and historically. The paper considers and clarifies the notable presence of language in its use in historical context of this tragedy.